Training systems affect spatial distribution of Korla fragrant pear (Pyrus sinkiangensis Yu) fruits by altering canopy structure and light distribution - Yan, Pan; Deng, Yonghui; An, Shi-jie; Ma, Ling; Li, Tianle; Chen, Qi-ling; Zheng, Qiangqing (Frontiers in Plant Science, 2025)
ObjectiveThis study aims to elucidate the relationship between canopy structure and fruit spatial distribution, establish a model linking canopy light distribution with fruit positioning, and identify optimal training strategies for consistently high yield. The findings provide a theoretical foundation for optimizing modern cultivation practices in Korla fragrant pear orchards.MethodsFour training treatments were established: precision pruning, reduction, falling head, and thinning. Canopy structural parameters and light distribution were measured, along with canopy light interception (ALI). Fruit number and individual fruit weight were recorded at different canopy positions. Correlation analysis was used to revealing the relationship between canopy structure, light distribution, and spatial distribution of fruits.Results(1) Canopy Structure: Reduction and falling head effectively controlled canopy spread, significantly reduced the proportion of long branches while increased the proportion of middle branches. Thinning, however, increased the proportion of long branches, total branch length and average branch length, led to significant expansion in canopy diameter, surface area, and volume. (2) Light Distribution: Reduction increased average light interception (ALI) by 15%, while thinning improved ALI by 11% significantly, enhanced light availability across different canopy aspects, falling head notably improved light penetration in the middle and lower canopy layers. Persistent low-light zones (ALI < 300 μmol·m-²·s-¹) were identified in the lower canopy, inner canopy, and inter-tree spaces, highlighted key areas for light optimization. (3) Fruit Spatial Distribution: Smaller canopies had fewer but more uniformly distributed fruits. As canopy size increased, light interception and photosynthesis improved, total fruit yield improved, however, spatial heterogeneity intensified, with fruit-bearing zones shifted outward and upward, reduced carbon allocation uniformity. (4) Yield Correlations: Two canopy structural parameters showed significant negative correlations with consistently high yield traits, while ten exhibited positive correlations. Tree height, canopy surface area, and total branch length had the strongest positive associations with total yield. (5) Key Relationship: The correlation between light distribution and fruit spatial distribution strengthened significantly with canopy expansion.ConclusionThe influence of canopy structure and light distribution on fruit spatial distributions depends on canopy size. For small canopies, canopy structure serves as the dominant factor affecting fruit distribution, while in large canopies, light distribution becomes the primary driver. Accordingly, distinct canopy management strategies should be adopted, small canopies should focus on increasing canopy surface area and total branch length, to increase fruiting sites and enhance yield, large canopies require optimizing light distribution to improve fruit spatial uniformity. Thinning promoted flower bud formation significantly by increased the proportion of long branches and lateral branch number, thereby optimized consistently high yield traits.